Diagnosing the Philippine economy toward inclusive growth - Canlas, Dante B.; Khan, Muhammad Ehsan; Zhuang, Juzhong (Published for the Asian Development Bank by Anthem Press, 2009)
'Diagnosing the Philippine Economy' describes the conditions that depress economic growth in the Philippine economy and their causes and potential solutions.